2008
DOI: 10.1080/01612840802319860
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Quit Smoking in Rural Communities

Abstract: The purpose of this study was to determine psychosocial and demographic factors associated with readiness to quit smoking among rural current and recent former smokers. This cross-sectional study of 333 rural adults was part of a larger quasi-experimental study testing the effect of a population-based Quit and Win Contest on quitting. Readiness to quit, partner support to quit smoking, stressful life events, depressive symptoms, and demographic characteristics were measured via a phone interview three months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Most of these themes are consistent with the findings of similar research conducted in Appalachia 2329 and with rural or disparate populations 3, 10, 30, 31 but there are novel ideas that offer intriguing insights and implications for further research and intervention development in rural communities.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Most of these themes are consistent with the findings of similar research conducted in Appalachia 2329 and with rural or disparate populations 3, 10, 30, 31 but there are novel ideas that offer intriguing insights and implications for further research and intervention development in rural communities.…”
Section: Discussionsupporting
confidence: 73%
“…31 Similarly, Rayens found that a major illness could influence readiness to quit smoking. 10 However, in a study of smoking relatives of lung cancer patients, 91% of smoking family members still smoked following an educational intervention about the benefits of smoking cessation. 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Friends and family who encourage quitting have been described as important motivators to smoking cessation in the region. 15,16 Lack of access to parents’ cigarettes also has a positive impact on preventing youth uptake of smoking in Appalachia. 8 Physician recommendations to quit smoking have also been correlated with cessation attempts in Kentucky.…”
Section: Determinants Of Smoking Cessation In Appalachiamentioning
confidence: 99%
“…Most research has focused on cessation-harnessing support to help smokers who are already in treatment programs and have high baseline levels of quitting readiness (Cohen & Lichtenstein, 1990; Park et al, 2012; Westmaas et al, 2010). Two studies enrolling community samples of smokers found that social support for quitting was associated with increased stage of change, a conventional measure of quitting motivation (Rayens, Hahn, & Hedgecock, 2008; Sorensen, Emmons, Stoddard, Linnan, & Avrunin, 2002). Further, a population-based survey study (Burris et al, 2013) observed that social support was greater among smokers who want to quit now than those not ready to quit immediately.…”
Section: Introductionmentioning
confidence: 99%